Pengaruh Ekspektasi Pendapatan dan Lingkungan Keluarga terhadap Minat Berwirausaha Peserta Didik - Andi Rinda Oktariani; Mustari; Agus Syam; Muhammad Hasan; Inanna (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
This study aims to determine the influence of income expectations and the family environment on the entrepreneurial interests of students of Madrasah Aliyah Pompanua District Ajangale Bone District. This research is categorized as quantitative descriptive research with correlation approach. The population in this study as many as 188 students of class XI and class XII in Madrasah Aliyah Pompanua District Ajangale Bone district and obtained a sample of 65 students. Data collection is done by observation and questionnaire techniques. The analysis technique used is multiple linear regression. The results of this study showed that income expectations and the family environment have a positive and significant effect on the entrepreneurial interests of students in Madrasah Aliyah Pompanua, Acaraale District, Bone Regency, both partially and simultaneously. In this study, the most dominant variable was income expectations because it had a higher regression coefficient value than family environment regression coefficient value.